The fox and the hound ; and The fox and the hound II [videorecording (DVD)]. - Stevens, Art; Berman, Ted, 1919-2001; Rich, Richard; Kammerud, Jim; Rooney, Mickey; Russell, Kurt; Bailey, Pearl; Bobo, Jonah; Fahn, Harrison; McEntire, Reba; Swayze, Patrick; Mannix, Daniel P. (Daniel Pratt), 1911-1997 (Walt Disney Studios Home Entertainment ; Distributed by Buena Vista Home Video, 2011)
Two friends discover that they are meant to be enemies when they grow up.